Media Social Media Metrics in the context of Metrics Studies of Information - Delbianco, Natalia Rodrigues [UNESP] (Univ Federal Parana, Dept Ciencia & Gestao Informacao, 2023)
Introduction: this research is part of the field of Scientific Communication, more precisely in Information Metrics Studies, because it addresses Social Media Metrics Studies, which are underexplored within the context of Information Science. Therefore, the research aims to understand, in general, the presence of Social Media Metrics Studies in the field of Information Metrics Studies in order to contribute to the theoretical-conceptual knowledge of the subject. Method: it is characterized as a theoretical study with a descriptive-exploratory approach. Results: among the main results of this study are the theoretical development and presentation of the field of Social Media Metrics Studies, its indicators, and especially the group of social connectivity indicators. Conclusion: the research presented theoretical viewpoints on social media and networks, as well as Social Media Metrics Studies, including a compilation of their indicators, in an attempt to provide more theoretical support for future research, as currently, they tend to consider only altmetric and webometric viewpoints.
Keywords: Social media; Social networks; Metric Studies of Social Media; Metric Studies of Information; Scientific Indicators